Child health and schooling achievement in Bangladesh. Issue 1 (7th January 2014) - Khanam, Rasheda
Abstract : Purpose: – This paper aims to examine the impact of child health (measured by nutritional status) on schooling performance of Bangladeshi children. Design/methodology/approach: – The data set used in this study comes from a survey titled "Micronutrient and Gender Study (MNGS) in Bangladesh". The survey was administered by the International Food Policy Research Institute (IFPRI). The author controls for the potential endogeneity of child health by an instrumental variables approach. The results indicate that the impact of child health on school achievement will be overestimated if endogeneity of child health is ignored. Findings: – The results reveal that child health has significant effects on school enrolment and grade attainment, although it does not affect the current school attendance. The impact of child health is stronger for school enrolment compared to grade attainment. Originality/value: – This study improves the understanding on the relationship between child health and schooling in several ways. First, the author controls for the potential endogeneity of child health by an instrumental variables approach. The chosen instrumental variables (i.e. heights of father and mother) are strong predictors of child health and satisfy the validity test. Second, this study examines the effects of child health on wide ranges of schooling measures: enrolment, attendance and attainment.